TOL plasmid pWW0 in constructed halobenzoate-degrading Pseudomonas strains: enzyme regulation and DNA structure. - Jeenes, D J (1982)
WR211 and WR216 are derivatives of halobenzoate-degrading Pseudomonas sp. strain B13 into which the 117-kilobase TOL degradative plasmid pWW0 has been transferred from Pseudomonas putida mt-2. WR211 has lost the ability to grow on the TOL-specific substrate m-xylene but retains the ability to grow on its metabolite, m-toluate. An analysis of the induction of enzymes was consistent with WR211 carrying a nonfunctional regulatory gene, xy1R, WR216 is a spontaneous derivative of WR211 which grows on one of the TOL substrates and yet expresses the nonspecific toluate oxidase, which enables it to grow on the novel substrate 4-chlorobenzoate. In addition to the xy1R lesion inherited from WR211, WR216 appears to carry a mutation in the structural gene for catechol 2,3-oxygenase, xy1E. The plasmids in both strains were analyzed by restriction endonuclease digestion. pWW0-1211 in WR211 has a large deletion (39 kilobases) compared with pWW0 and appears to be identical to a previously described plasmid (pWW0-8) which encodes none of the TOL degradative functions. pWW0-1216 in WR216 has undergone a major structural reorganization relative to its parent, pWW0-1211. This plasmid has a smaller deletion (19 kilobases), which is staggered relative to the deletion in pWW0-1211, and in addition it has two 3-kilobase insertions of unknown origin, one of which appears to cause the xylE mutation.